Pacran®, a powder obtained from cranberries, and defence against bacterial pathogens in the lower urinary tract: Evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Montaña Cámara; Jacqueline Castenmiller; Stefaan deHenauw; Karen‐Ildico Hirsch‐Ernst; Angeles Jos; Alexandre Maciuk; Inge Mangelsdorf; Breige McNulty; Androniki Naska; et al. (EFSA Journal)
Abstract Following an application from Givaudan, submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Italy, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to Pacran® and defence against bacterial pathogens in the lower urinary tract. The Panel considers that the food Pacran®, a powder obtained from cranberries, is sufficiently characterised. Defence against bacterial pathogens in the lower urinary tract is a beneficial physiological effect. The applicant identified two human intervention studies which investigated the effect of Pacran® on the incidence of urinary tract infections (UTI) as being pertinent to the claim. In weighing the evidence, the Panel took into account that one human intervention study showed a beneficial effect of Pacran® consumed daily at doses of 500 mg for 6 months on the incidence of symptomatic, culture‐confirmed UTI in women with a history of recurrent UTI, whereas such an effect was not consistently observed in another study under similar conditions. The Panel also took into account that limited evidence has been provided for a mechanism by which Pacran® could exert the claimed effect. The Panel concludes that the evidence provided is insufficient to establish a cause and effect relationship between the consumption of Pacran® and the defence against bacterial pathogens in the lower urinary tract.